The Dutch Position in World War II in Sedjarah Umum Textbook by Anwar Sanusi (History Department, Semarang State University and Historian Society of Indonesia, 2021)
Abstract: This article discusses Sedjarah Umum written by Anwar Sanusi, namely the historiography of history textbooks in transitional historical records. At the beginning of Indonesia's independence, textbooks for history subjects was faced a non-centric and Indonesian-centric examination style. Neerlando-centric is a style that studies old historiography that is used mostly by colonial education. Choosing Indonesia-centric was a new style of writing after independence which had the purpose of writing a history that made the Indonesian nation the main actor. Still, it did not solve the history of Europeans in the Indies. The method used in this study is discourse analysis. The results of the study in this paper are (1) The writing of the Sedjarah Umum textbook written by Anwar Sanusi can be published using Neerlando centric and Indonesian centric; (2) The Dutch in World War II were shown as mediators and victims; (3) Indonesia-centric is indicated by mentioning Indonesia as a unified country. This study also compares textbooks published by the Sedjarah Umum of Anwar Sanusi's works based on the analysis: there are Neerlando centric and Indonesia-centric approaches.Â Abstrak: Artikel ini membahas tentang historiografi Sedjarah Umum karangan Anwar Sanusi yaitu historiografi buku ajar sejarah dalam masa transisi. Pada awal kemerdekaan Indonesia, buku teks pelajaran sejarah dihadapkan pada gaya ujian non sentris dan Indonesia sentris. Neerlando-sentris adalah gaya yang mempelajari historiografi lama yang sebagian besar digunakan oleh pendidikan kolonial. Memilih Indonesia-sentris adalah gaya penulisan baru setelah kemerdekaan yang bertujuan untuk menulis sejarah yang menjadikan bangsa Indonesia sebagai pemeran utamanya, tetapi tidak menyelesaikan sejarah bangsa Eropa di Hindia Belanda. Metode yang digunakan dalam penelitian ini adalah analisis wacana. Hasil penelitian dalam makalah ini adalah (1) Penulisan buku teks Sedjarah Umum karangan Anwar Sanusi diterbitkan dengan menggunakan Nerlando centric dan Indonesian centric; (2) Belanda dalam Perang Dunia II ditampilkan sebagai mediator dan korban; (3) Indonesia-sentris ditunjukkan dengan menyebut Indonesia sebagai negara kesatuan. Studi ini juga membandingkan buku teks Sedjarah Umum Anwar Sanusi berdasarkan pendekatan Neerlando centric dan Indonesia-centric.Â Â